Knowledge Attitude & Practices towards Voluntary Blood Donation among Medical Students in Barabanki - Chopra, Deepak; Jauhari, Nidhi (Indian Journal of Community Health, 2015)
Introduction: Blood Donation can save million lives. Voluntary blood donations are the cornerstone of a safe and adequate supply of blood and blood products. The safest blood donors are voluntary, non-remunerated blood donors from low-risk populations. Objectives: The present study was undertaken with an aim to understand the factors like knowledge, attitude and practices associated with voluntary blood donation among the medical students in a medical college. Materials & Methods: This is a cross sectional study with a sample size of 278. A pre-tested semi structured questionnaire was used to assess the level of knowledge, attitude and practices regarding blood donation in the study subjects. The data was analyzed by applying suitable statistical methods. Results: The knowledge about the recommended age and interval of blood donation was 90 % & 48.9% respectively. Nearly 23% of students had ever donated blood and the majority of subjects (56.5%) did not have an opportunity to donate blood. 75.54 % of students were willing to donate blood at the time of study. Conclusion: Creating the opportunities regarding the blood donation may lead to the achievement of goal of 100% non-remunerated voluntary blood donation.